The triumph of the snake goddess - Haq, Kaiser; Doniger, Wendy (Cambridge, Massachusetts : Harvard University Press, 2015)
The Triumph of the Snake Goddess, a prose translation by the scholar and poet Kaiser Haq, is the first comprehensive retelling of this epic in modern English. Haq's Prologue explores the oral, poetic, and manuscript traditions, and Wendy Doniger's Introduction examines the significance of snake worship in classical Sanskrit texts.
Includes bibliographical references.
ENH
Keywords: Manasa (Hindu deity)